The Red Fox 1980
DOI: 10.1007/978-94-017-5592-4_17
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Spread of a Wildlife Rabies Epidemic in Europe

Abstract: The control of rabies in wildlife by reducing the fox population has led in Europe to inconsistent results, since little was known of the dynamics of the fox population and the interaction between rabies epidemics, host populations, and control measures. As part of the WHO/FAO Coordinated Research Programme on Wildlife Rabies in Europe, data on epidemics and persisting reservoirs of the disease were processed by computer. The results led to a better understanding of the mechanism of spread of the epidemic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 2 publications
2
21
0
Order By: Relevance
“…This corresponds to observations in the field (e.g. Bogel and Moegle 1980). Another remarkable thing is that for somewhat larger densities the velocity of rabies expansion slightly decreases with increasing fox population density.…”
Section: Rabies (Lyssavinus Spp)supporting
confidence: 89%
“…This corresponds to observations in the field (e.g. Bogel and Moegle 1980). Another remarkable thing is that for somewhat larger densities the velocity of rabies expansion slightly decreases with increasing fox population density.…”
Section: Rabies (Lyssavinus Spp)supporting
confidence: 89%
“…This reflects population dynamics in the face of an epizootic of fatal disease and the exhaustion of susceptible animals to sustain the force of infectivity. This is consistent with the 48-mo period of the first epizootic phase in the predictive modeling and other temporal and spatial analysis of wildlife rabies (Bö gel et al, 1976;Hanlon et al, 1999;Guerra et al, 2003). Since that time, a less dramatic, approximate 5-yr cycle may be in evidence, with geotemporal hot spots of intensified activity occurring.…”
Section: Discussionsupporting
confidence: 78%
“…The shift of the front has varied between a temporary standstill and a progression of 60-80 km per year. In a computer analysis by Bogel et al (21), the mean monthly distance in which new cases were found beyond the frontline was 4.8 km, regardless of the relative fox population density above a critical threshold. Maximum monthly spread was 20 km.…”
Section: The Spread Of Rabiesmentioning
confidence: 97%
“…In most surveys a lower percentage of rabies infected foxes is found. This is mainly due to underreporting in foxes and The analysis of the frontwave shows that foxes bring the infection into new areas (13,16,21,25). Of all rabies cases appearing before a given monthly frontline, 97.2 per cent are foxes, whereas Annual kill by hunting, accident and disease Rabies infected foxes FIGURE 5.…”
Section: Involvement Of Animal Speciesmentioning
confidence: 99%